Mode of presentation and performance of serology assays for diagnosing celiac disease: A single-center study in the United Arab Emirates - Shatnawei, Abdullah; AlNababteh, Asma H.; Govender, Romona Devi; Al-Shamsi, Saif; AlJarrah, Ammar; Al-Rifai, Rami H. (Frontiers in Nutrition, 2023)
Objective To characterize patients with celiac disease (CD), examines the clinical spectrum of CD, and evaluate the performance of serologic tests used for CD screening, in the United Arab Emirates (UAE). Method Medical charts of patients received at the Digestive Diseases Institute of Cleveland Clinic Abu Dhabi from January 2015 to December 2020 were reviewed. Patients who were screened for four serologic biomarkers (anti-tissue transglutaminase IgA [Anti-tTG-IgA], anti-tissue transglutaminase IgG [Anti-TtG-IgG], anti-deamidated gliadin peptide IgG [Anti-DGP-IgG], and anti-deamidated gliadin peptide IgA [Anti-DGP-IgA]) were included. Histopathology was performed on patients with the seropositive test. Marsh score >1 considered to confirm CD. Characteristics of the Anti-tTG-IgA seropositive patients were described and that correlated with histopathologically-confirmed CD were explored. Results Of the 6,239 patients, 1.4%, 2.9%, 4.7%, and 4.9%, were seropositive to Anti-tTG-IgG, Anti-TtG-IgA, Anti-DGP-IgA, and Anti-DGP-IgG, respectively. Overall, 7.7% were seropositive to either of the four biomarkers. Of the biopsy-screened 300 patients, 38.7% (1.9% of the total serologically screened) were confirmed with CD. The mean age of Anti-TtG-IgA seropositive patients was 32.1 ± 10.3 SD years, 72% of them were females, and 93.4% were Emirati. In those patients, overweight (28.7%) and obesity (24.7%) were common while 5.8% of patients were underweight. Anemia prevalence was 46.7%, 21.3% had Gastroesophageal reflux disease (GERD), 7.7% with autoimmune thyroid disease, 5.5% (type 1), and 3.3% (type 2) were diabetic. Vitamin D deficiency was observed in 47.8% of the Anti-TtG IgA seropositive patients. Twelve (10.3%) histopathologically-confirmed CD patients were seronegative to Anti-TtG-IgA but seropositive to anti-DGP-IgA and/or Anti-DGP-IgG. Body mass index, GERD, autoimmune thyroid disease, type 1 diabetes, asthma, hemoglobin, and vitamin D concentration, were all correlated with biopsy-confirmed CD (P<0.05). Compared to the gold-standard biopsy test, Anti-TtG-IgA had the highest sensitivity (89.7%) and specificity (83.7%). Conclusion Three and two of every 100 patients were serologically (anti-tTG-IgA positive) and histopathologically diagnosed with CD, respectively. Although Anti-TtG-IgA is the most sensitive, specific, and commonly used test, one of every ten histopathologically-confirmed patients and Anti-tTG-IgA seronegative were seropositive to Anti-DGP. To avoid missing patients with CD, a comprehensive serological investigation covering DGP-IgG/IgA is warranted.